2018
DOI: 10.1111/jog.13768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of menstrual pain on the academic performance and participation in sports and social activities in Turkish university students with primary dysmenorrhea: A case control study

Abstract: The results of the present study present that PD negatively influences academic performance and participation in sports and social activities. Furthermore, pain characteristics differed among the patients with mild, moderate and severe pain. There is a need for further studies that improve treatment options for PD in order to minimize the influence of pain on academic performance and social activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 24 publications
3
48
3
3
Order By: Relevance
“…The most common pain intensity reported was the severe one (52.5%) while only 13.6% students reported experiencing mild pain. This finding differs from what was reported previously in which the prevalence of severe intensity was much lower e.g., [2,19,26]. This discrepancy could be explained by the difference in pain perception across different cultures.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The most common pain intensity reported was the severe one (52.5%) while only 13.6% students reported experiencing mild pain. This finding differs from what was reported previously in which the prevalence of severe intensity was much lower e.g., [2,19,26]. This discrepancy could be explained by the difference in pain perception across different cultures.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research have shown a higher risk for dysmenorrhea in women with lower BMI, smoking behavior and a longer cycle but a lower risk in women that exercise regularly [10]. However, there are also studies that did not find differences in dysmenorrhea in relation to these characteristics e.g., [19,29]. This discrepancy across literature might be due to the different ages of the participants, cultures, sample size, definition of dysmenorrhea or scale measuring pain intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have identified how pain can affect people, for example, headaches are known to decrease the academic performance of university students [4]. More concretely, menstrual pain increases absenteeism and decreases academic performance [5,6]. However, most previous studies are based on studying dysmenorrhea alone, while few studies have focused on analyzing other menstrual experiences in depth, such as fatigue, nausea, diarrhea, headache, dizziness, feeling depressed, sleep disorders, or irritability.…”
Section: Introductionmentioning
confidence: 99%
“…1 Dysmenorrhea is considered as a lower abdominal or pelvic pain appears just before and/or during menstruation and lasts about 2448 hours. 2 It is a common condition with prevalence rates between 50% and 91% in women. The daily life of women with menstrual pain can be adversely affected by pain and pain accompanying symptoms.…”
Section: Referencesmentioning
confidence: 99%